Hunter-gatherer Ireland : making connections in an island world - Warren, Graeme (Oxbow Books, 2022)
Explores the Irish Mesolithic - the period after the end of the last Ice Age when Ireland was home to hunter-gatherer communities, mostly from about 10,000-6,000 years ago. At this time, Ireland was an island world, with striking similarities and differences to its European neighbours - not least in terms of the terrestrial ecology created by its island status. To understand the communities of hunter-gatherers who lived there, it is essential that we consider the connections established between people and the other beings and materials with which they shared the world and through which they grew into it. Understanding the Mesolithic means paying attention to the animals, plants, spirits and things with which hunting and gathering groups formed kinship relationships and in collaboration with which they experienced life. 0The book closes with a reflection on hunting and gathering in Ireland today. The overriding aim of the book is to provide a point of entry into the lives of the Irish Mesolithic, to show the different ways in which people have lived on this island, and to show how we might narrate those lives.